PENGARUH PEMAHAMAN E–COMMERCE, PEMAHAMAN SISTEM INFORMASI AKUNTANSI, DAN EKSPEKTASI PENDAPATAN TERHADAP MAHASISWA YANG BERWIRAUSAHA - Pramana Putra, Ida Bagus; Sari Widhiyani, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
Entrepreneurial activities must certainly be able to take advantage of all existing facilities, one of which is the use of technology, namely E-Commerce and Accounting Information Systems. However, before being able to use the technology, entrepreneurs must first understand how the technology operates so that when the technology is used later it will provide convenience for entrepreneurs in entrepreneurship. Income Expectations also play a role in entrepreneurship where high income expectations will motivate an entrepreneur to become more entrepreneurial. The topic of entrepreneurship is being hotly discussed among students, because there are not a few students who are entrepreneurs in the midst of their busy college days. The purpose of this study is to provide empirical evidence related to the influence of Understanding E-Commerce, Understanding Accounting Information Systems and Income Expectations on Entrepreneurial Students. The population in this study was 35 students, with sampling using a saturated sampling technique, namely the entire population was used as a research sample. The data analysis technique in this study used multiple linear regression analysis. The results showed that Understanding E-Commerce, Understanding Accounting Information Systems and Income Expectations had a positive effect on Entrepreneurial Students.